Upaya Pengentasan Kemiskinan Melalui Program Nasional Lumbung Ikan Nasional (LIN) Di Kepulauan Aru, Propinsi Maluku - Hendri D. Hahuri; Max R. Wenno; Johanes M. S. Tetelepta; Billy J. Camerling; Febryano Saptenno; Fredy Louhenapessy; Revi W. Silooy; Hermi Oppier (Universitas Mathla'ul Anwar Banten, 2022)
POVERTY ALLEVIATION EFFORTS THROUGH THE NATIONAL FISH BARN PROGRAM IN ARU ISLANDS, MALUKU PROVINCE. The potential of abundant fishery resources is expected to be one way to overcome poverty, especially for the coastal communities, mainly those living in archipelagic areas. However, in Aru Islands, Maluku Province, there is an inverse comparison. Although they have the potential of abundant fishery resources, to this date, the local community are still living in poverty. This community service is expected to be an effort to alleviate poverty through the National Fish Barn (Lumbung Ikan Nasional (LIN)). The method used was a combination of socialization and assistance for fishermen in Karangguli Village, Wokam Village and Jabulenga Village. The results are in the form of identification of problems faced by the fishermen, solutions and potentials of the fishery sector through the National Fish Barn program as a way to overcome the poverty. The fishermen were still struggling with the poverty although they lived close to the abundant fishery resources. The presence of National Fish Barn in Maluku, including in the Aru Islands, is expected to side with the community so that they can improve their level of welfare.